Functional disabilities and nursing home admittance - KOH, Seng Kee Benedict (Institutional Knowledge at Singapore Management University, 2012)
This paper examines how inability to perform activities of daily living relates to the risk of nursing home admission over older adults' life courses. Using longitudinal data on persons over age 50 from the Health and Retirement Study, we show that aging one year boosts the probability of having two or more disabilities by 9 to 12 percent in a multivariate logistic model. Moreover, at least three-fifths of all 65-year-old men and three-quarters of women will experience disability levels during their remaining lifetimes severe enough to trigger nursing home admission. Our analysis also suggests that certain types of disability are more important than others in predicting nursing home admittance and use, which has implications for the design and benefits triggers for long-term care insurance programs.